The Aplication of Learning Cycle Model to Improve Science Process Skill of Class X-2 Student of SMA Negeri 3 Surakarta in Academic Year 2010/2011 - Dewi Retnaningati; Maridi Maridi; Bowo Sugiyarto (Universitas Sebelas Maret, 2013)
The purpose of this research is to improve science process skill of class X-2 student of SMA Negeri 3 Surakarta 2010/2011 academic matter on subject matter Ecosystem and Environment by appliying Learning Cycle model. This research refers to The Classroom Action Research with subject were 34 students from class X-2 of SMA negeri 3 Surakarta 2010/2022 academic year. The sources of data consist of information from teacher and student, places and events that happened during teaching and learning process, and also some documents. The data of research is collected by using observation sheet, test, questionnaire, interview, and documents. The data is analyzed in qualitative descriptive method. The validity of data is verified through triangulation technique of data collecting method. The result of this research shows that there has been increment percentage of the questionnaire and observation result in every aspect which includes involvement, team work, and responsibility aspects. The result of this research shows that there has been increment percentage of science prosess skill aspect mastery level from 57,03% on presequence become 74,85% on first sequence and 79,89% on second sequence. If it considerate from science process skill indicator, it has been increament percentage of science process skill indicator mastery level too from 56,59% on presequence become 74,08% on first sequence, and 79,88% on the second sequence. The reflection of the first sequence shows that students having low of responsibility in achieving the learning goal, so the researcher gave further treatment in sequence II. It can be concluded from the research that Learning Cycle application can improve science process skill of class X-2 student of SMA Negeri 3 Surakarta 2010/2011 academic year. Key Words: learning cycle model, science process skill